Two intertwined compartments coexisting in sporadic conventional colon adenomas - Rubio, Carlos A. (Intest Res, 2021)
Sporadic conventional colon adenomas are microscopically built of 2 intertwined compartments: one on top, harboring the dysplastic tissue that defines their histo-biomolecular attributes, and the other below, composed of non-dysplastic crypts with corrupted shapes (CCS). The CCS of 306 colon adenomas revealed asymmetric, haphazardly-distributed proliferating cell-domains (PC). In contrast, the PC-domains in normal controls were symmetric, being limited to the lower thirds of the crypts. In 28% out of 501 sporadic conventional adenomas, foci of p53-upregulated dysplastic tissue were found. The CCS in 30% of 108 sporadic adenomas showed p53-upregulated single cells, suggesting mounting somatic mutations. No p53-upregulated cells were found in the crypts of controls. In polypoid adenomas, the mucosa of the stalk without dysplastic tissue on top disclosed CCS with asymmetrical PC-domains and single p53-upregulated cells. The latter observations suggested that CCS had developed prior to and not after the growth of the dysplastic tissue on top. CCS were also found below colon adenomas in carcinogen-treated rats. It is concluded that the 2 intertwined histo-biological compartments of sporadic conventional colon adenomas are probably interdependent components. These findings may open new directions aimed to uncover the link between the normal colonic mucosa and the histogenesis of, conventional adenomas.